Predictive Factors of Poor Outcome in Road Traffic Injures; a Retrospective Cohort Study - Hatamabadi, Hamid Reza; Shojaee, Majid; Kashani, Parvin; Forouzanfar, Mohammad Mehdi; Aghajani Nargesi, Dorrin; Amini Esfahani, Mohammad Reza (Archives of Academic Emergency Medicine, 2017)
Introduction: Road traffic injuries (RTI) are among the most important health problems worldwide as they cause more than 1.2 million deaths and 50 million injuries each year. Therefore, the present study aims to evaluate the outcome and aftermath of RTI in those who were injured and hospitalized due to a traffic accident. Methods: In the present retrospective cohort study with a one-year follow-up, data were extracted from the profiles of the RTI hospitalized patients. Outcome of the patients was evaluated at the time of discharge and 1-year later including their living state, presence of a disability or complete recovery. Results: 1471 patients were studied (mean age of 32.8Â±17.0; 80.3% male). 571 (38.8%) had mild disability, 684 (46.5%) moderate disability, and 85 (5.8%) had severe disability at the time of discharge. In the end, 53 (3.6%) died. In the 1-year follow-up, 194 (13.2%) had mild disability, 43 (2.9%) had moderate disability, 9 (0.6%) had severe disability, and 7 (0.5%) were in a vegetative state. Presence of an underlying disease (p=0.03), loss of consciousness for more than 24 hours (p=0.04), spinal injury (p=0.002), presence of multiple trauma (p=0.01), increased ISS (p<0.001), need for ventilator (p<0.001), and organ injuries during hospitalization (p<0.001) are independent factors that increase the risk of poor outcome in RTI patients. Conclusion:Â Based on the results of the present study, underlying illnesses, loss of consciousness for more than 24 hours, spinal injury, multiple trauma, increased ISS, need for ventilator, and organ injuries during hospitalization were independent factors that increased the probability of poor outcome in RTI injuries.